PENGEMBANGAN MODUL TEKNIK GAMBAR MANUFAKTUR KELAS XI TP SMK TKM TEKNIK PURWOREJO - Murwanto; suparmin; setuju setuju (JURNAL VOKASI DEWANTARA (JVD), 2021)
This study aims to determine the feasibility of the Manufacturing Image Engineering Module which can be used as teaching material in Class XI TP at the Purworejo Technical TKM Vocational School. This research uses a type of Research and Development to validate and develop products. The Development Model used in this study includes: 1) searching for potentials and problems, 2) gathering information, 3) product design, 4) design validation, 5) design revisions, 6) product testing, 7) product revisions, 8) usage tests , 9) product revisions, 10) mass product / product dissemination . Data analysis uses three tests, namely material experts, media experts, field tests and reliability tests. The results showed that the Manufacturing Engineering Technique module was declared feasible as a Class XI TP teaching material at the Purworejo Technical TKM Vocational School. This is based on the results of the following analysis: (1) Based on the aspects of self- intruction, self contained aspects, stand alone aspects, adaptive aspects and user friendly aspects, the average total score was 3.20 so that it was included in the "Eligible" category, (2) based on aspects format, organizational aspects, aspects of attractiveness, aspects of shape and size of letters, aspects of empty space (space), and aspects of consistency the total score of each instrument amounted to 19.32 / 6 = 3.22 from a maximum score of 4.00 so that it was included in the category "Decent". (3) based on the average total score of each aspect of the material aspect, the media aspect and the module learning aspect amounted to 3.29 + 3.34 + 3.23 = 9.86, the average total score for each instrument was 9.86 / 3 = 3, 28 of the maximum score of 4.00 so that it is included in the category of "very decent", (4) the results of reliability show the number 0.851, the input instruments for students fall into the category of "very reliable".